“CONFLICTOS JURÍDICOS QUE SE ORIGINAN POR LA FALTA DE DELIMITACIÓN EN LA LEY DE INQUILINATO DEL MONTO DEL CANON DE ARRENDAMIENTO MENSUAL - Bravo Lozano, Paola Gabriela (2016)
This thesis entitled "“Conflictos jurídicos que se originan por la falta de delimitación en la ley de inquilinato del monto del canon de arrendamiento mensual.” Is framed according to the required institutional guidelines. Why to begin addressing the problem thought advisable to publish the conceptualizations of topics such as: the lease, classification, requirements, elements and ways to celebrate a lease, according to these Tenancy Act, the Civil Code, as well as the definitions that some writers have about equally definitions of the rental fee, city limits and just price is found. Then I make a historical review of this law starting from its origins and its evolution over time, up to now, to continue with a critical analysis of legal and doctrinal articles covered by the RTA. With the aim of knowing what is happening elsewhere in this issue I conducted an analysis and comparison of the laws of other countries such as Venezuela, Colombia, Honduras and Spain. Materials and methods used to perform this research, population and sample the selection of respondents described later to proceed to issue the results of surveys, like the opinions of the respondents, as they conducted five interviews with lawyers, both surveys and interviews with their respective analysis. 5 It continues with the verification of objectives, which by the way everyone was checked, as was proven the hypothesis which turned out to be positive, and finally a legal analysis of the items considered obsolete is to issue the merits of proposal amendments to the Tenancy Act. Finally conclusions and recommendations are made, all based on the results of field research, culminating giving legal reform proposal that the law in question both need